2014
DOI: 10.1007/s10404-013-1328-0
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic fractionation of binary suspensions moving past a line of microposts

Abstract: We investigate the motion of suspended particles past a single line of equally spaced cylindrical posts that is slanted with respect to the driving force. We show that such a one-dimensional array of posts can fractionate particles according to their size, with small particles permeating through the line of posts but larger particles being deflected by the steric barrier created by the posts, even though the gaps between posts are larger than the particles. We perform characterization experiments driving monod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Comparison of the data collected with microfluidic data in Ref 26 and Ref. 35 showing good agreement across different length scales. The dashed lines correspond to constant non-dimensional roughness 10 -3 , 10 -2 , and 10 -1 from the bottom.…”
Section: B Scaling Behaviormentioning
confidence: 57%
“…Comparison of the data collected with microfluidic data in Ref 26 and Ref. 35 showing good agreement across different length scales. The dashed lines correspond to constant non-dimensional roughness 10 -3 , 10 -2 , and 10 -1 from the bottom.…”
Section: B Scaling Behaviormentioning
confidence: 57%
“…In addition, the particles experience an electrophoretic force that depends on their charge, but their motion is usually dominated by the electroosmotic flow, specially in buffered solutions. [13][14][15][16] The direction of the driving field is controlled by the orientation of the PDMS channel with respect to the array of obstacles. Therefore, we performed experiments for different angles of the driving field by changing the orientation of the channel, which was reversibly attached to the glass slide.…”
Section: Experimental Setup and Methodmentioning
confidence: 99%
“…Although DLD was initially introduced as a flow-driven, passive microfluidic method for size separation, we have shown in previous work that driving the particles by external forces also results in separation depending on the orientation of the force with respect to the array of obstacles. Specifically, we have successfully used gravity and electric fields to drive the separation of suspended particles in force-driven DLD (f-DLD) [28]- [31]. In their original work, Inglis et al observed two different types of trajectories, depending on the size of the particles: bump mode trajectories for larger particles and zigzag mode trajectories for smaller ones [32].…”
Section: Introductionmentioning
confidence: 99%